Auditory attention enhances processing of positive and negative words in inferior and superior prefrontal cortex. (November 2017) - Wegrzyn, Martin; Herbert, Cornelia; Ethofer, Thomas; Flaisch, Tobias; Kissler, Johanna
Abstract: Visually presented emotional words are processed preferentially and effects of emotional content are similar to those of explicit attention deployment in that both amplify visual processing. However, auditory processing of emotional words is less well characterized and interactions between emotional content and task-induced attention have not been fully understood. Here, we investigate auditory processing of emotional words, focussing on how auditory attention to positive and negative words impacts their cerebral processing. A Functional magnetic resonance imaging (fMRI) study manipulating word valence and attention allocation was performed. Participants heard negative, positive and neutral words to which they either listened passively or attended by counting negative or positive words, respectively. Regardless of valence, active processing compared to passive listening increased activity in primary auditory cortex, left intraparietal sulcus, and right superior frontal gyrus (SFG). The attended valence elicited stronger activity in left inferior frontal gyrus (IFG) and left SFG, in line with these regions' role in semantic retrieval and evaluative processing. No evidence for valence-specific attentional modulation in auditory regions or distinct valence-specific regional activations (i.e., negative > positive or positive > negative) was obtained. Thus, allocation of auditory attention to positive and negative words can substantially increase their processing in higher-order language and evaluative brain areas without modulating early stages of auditory processing. Inferior and superior frontal brain structures mediate interactions between emotional content, attention, and working memory when prosodically neutral speech is processed.